Gas around galaxy haloes - III: hydrogen absorption signatures around galaxies and QSOs in the Sherwood simulation suite - Meiksin, Avery; Bolton, James S.; Puchwein, Ewald (Oxford University Press, 2017)
Modern theories of galaxy formation predict that galaxies impact on their gaseous surroundings, playing the fundamental role of regulating the amount of gas converted into stars. While star-forming galaxies are believed to provide feedback through galactic winds, quasi-stellar objects (QSOs) are believed instead to provide feedback through the heat generated by accretion on to a central supermassive black hole. A quantitative difference in the impact of feedback on the gaseous environments of star-forming galaxies and QSOs has not been established through direct observations. Using the Sherwood cosmological simulations, we demonstrate that measurements of neutral hydrogen in the vicinity of star-forming galaxies and QSOs during the era of peak galaxy formation show excess Ly α absorption extending up to comoving radii of ∼150 kpc for star-forming galaxies and 300–700 kpc for QSOs. Simulations including supernovae-driven winds account for the absorption around star-forming galaxies but not QSOs.